(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
For a healthy pregnancy and delivery of a normal child, different group of medicines taken for each month of pregnancy is described in Ayurveda as Masanumasik Kashayas (monthly antenatal decoctions). Objectives: To assess the knowledge, attitude and practice of Ayurvedic practitioners regarding Masanumasik Kashayas. Methodology: Following ethical approval, a cross-sectional descriptive survey was conducted among Ayurvedic physicians from Mumbai region. Results: Of 130 questionnaires distributed, 120 physicians responded (92%). Although all the physicians were aware that Masanumasik Kashayasare described in the Samhitas, only 60% knew the number of Kashayas (decoctions). 85% knew the rationale for prescribing these Kashaya s(decoctions) and 93% agreed that these Kashayas (decoctions) improved pregnancy outcome. However, in clinical practice, 45% participants said that they prescribed Kashayas (decoctions) only in patients with bad obstetric history while 52.5% prescribed in regular ante-natal care. 83% preferred Vati (tablet) form rather than Kashaya (decoction) as patient compliance was better. All physicians who prescribed said that there were no adverse complaints and the pregnancy outcome was good. Conclusion: The study thus showed that all Ayurvedic practitioners were still well versed with Masanumasik Kashayas and prescribed these kashayas (decoctions) for a good pregnancy outcome in clinical practice with some modifications like usage of only 9 Kashayas (decoctions) and Vati form (tablet).